2021
DOI: 10.3389/fneur.2021.755827
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs in Symptomatic and Asymptomatic Carotid Stenosis

Abstract: Background: Specific microRNAs (miRs) have been implicated in the pathophysiology of atherosclerosis and may represent interesting diagnostic and therapeutic targets in carotid stenosis. We hypothesized that the levels of specific circulating miRs are altered in patients with symptomatic carotid stenosis (sCS) in comparison to those in patients with asymptomatic carotid stenosis (aCS) planned to undergo carotid endarterectomy (CEA). We also studied whether miR levels are associated with plaque vulnerability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…Moreover, upregulation of miR-92a could also be a non-invasive serum biomarker for ACAS, which might be involved in the inflammatory response by enhancing nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) [71,88] in the dysregulation of endothelial progenitor cells by targeting growth differentiation factor 11 (GDF11) via the SMAD2/3/FAK/AKT/eNOS pathway [71,89] and in the progression of atherosclerosis through the targeting of ABCA1 [71,90], as mentioned above for miR-106-5p. miR-92a has also shown higher plasma levels in symptomatic versus asymptomatic patients [84] as has been described in the previous paragraph, suggesting that the circulating concentration of miR-92a may gradually increase from healthy subjects to asymptomatic and symptomatic patients. Moreover, miR-342-5p was significantly overexpressed in asymptomatic serum patients, which positively correlates with IL-6 and TNFα and might be involved in the proliferation and differentiation of VSMCs downregulating PI3K regulatory subunit α (PI3KR1) [69,91].…”
Section: Mirnassupporting
confidence: 70%
See 1 more Smart Citation
“…Moreover, upregulation of miR-92a could also be a non-invasive serum biomarker for ACAS, which might be involved in the inflammatory response by enhancing nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) [71,88] in the dysregulation of endothelial progenitor cells by targeting growth differentiation factor 11 (GDF11) via the SMAD2/3/FAK/AKT/eNOS pathway [71,89] and in the progression of atherosclerosis through the targeting of ABCA1 [71,90], as mentioned above for miR-106-5p. miR-92a has also shown higher plasma levels in symptomatic versus asymptomatic patients [84] as has been described in the previous paragraph, suggesting that the circulating concentration of miR-92a may gradually increase from healthy subjects to asymptomatic and symptomatic patients. Moreover, miR-342-5p was significantly overexpressed in asymptomatic serum patients, which positively correlates with IL-6 and TNFα and might be involved in the proliferation and differentiation of VSMCs downregulating PI3K regulatory subunit α (PI3KR1) [69,91].…”
Section: Mirnassupporting
confidence: 70%
“…These results seem to suggest that there is no correlation between plaque and the serum miR-133a expression profile among SCAS and ACAS patients [81][82][83]. The other study of circulating miRNAs did not provide strong evidence for associations between specific miRNAs, but there was a certain tendency showing higher plasma levels of miR-92a, miR-145, miR-210, and miR-143 in symptomatic versus asymptomatic patients [84]. Further work is needed to elucidate the role of circulating miRNAs between SCAS and ACAS patients.…”
Section: Mirnasmentioning
confidence: 77%
“…There is limited data on the miRNAs acting as triggers for symptom development in patients with a significant ICAS. In the study by Grosse et al, the levels of several popular circulating miRNAs (miR-92a, miR-126, miR-143, miR-145, miR-155, miR-210, miR-221, miR-222, and miR-342-3p) were analyzed in patients with symptomatic and asymptomatic ICAS that were referred to CEA [ 124 ]. The study has not found miRNAs diagnostic for symptomatic ICAS, except from the trend to difference for miR-92a in multivariate analysis [ 124 ].…”
Section: Degree Of Carotid Plaque Patients With Asymptomatic and Symp...mentioning
confidence: 99%
“…In the study by Grosse et al, the levels of several popular circulating miRNAs (miR-92a, miR-126, miR-143, miR-145, miR-155, miR-210, miR-221, miR-222, and miR-342-3p) were analyzed in patients with symptomatic and asymptomatic ICAS that were referred to CEA [ 124 ]. The study has not found miRNAs diagnostic for symptomatic ICAS, except from the trend to difference for miR-92a in multivariate analysis [ 124 ]. The authors have not observed either the relationship between miRNAs expression levels and micro embolic signals that correspond to plaque fragility and distal embolization to cerebral arteries by debris released from the plaque [ 140 ].…”
Section: Degree Of Carotid Plaque Patients With Asymptomatic and Symp...mentioning
confidence: 99%